Rantai Nilai Jeruk Keprok (Citrus Reticulate) Soe di Kabupaten Timor Tengah Selatan Provinsi Nusa Tenggara Timur - Gregorius Gehi Batafor; Yason Edison Benu (Politeknik Negeri Lampung., 2020)
These study aims are analyzed the value chain after applying Soe tangerine cold storage technology. Qualitative and quantitative research methodologies, while data analysis techniques used the biological method and cost analysis. Value chain analysis shows that collectors' profits are IDR 5,306 per kg, retailer IDR 10,806 per kg, while farmers IDR 1,806 per kg. If the difference between each actor in the distribution chain is calculated, the farmer only receives an added value of IDR 2,250 per kg, while collecting traders IDR 5,750 per kg and retailers IDR 11,250 per kg. The RC ratio produced by farmers is 1.14, collecting traders 1.31, and retailers 1.45. Analysis of basic costs, cold storage for 3 months requires a fee of IDR 708,146 per kg. This value is lower compared to conventional storage of IDR 1,372 per kg. Based on interviews regarding price predictions for the next 3 months and shrinkage values, there is a significant difference between conventional storage and cold storage. The advantage of cold storage is greater than conventional storage, which is IDR 13,417 per kg while conventional storage is IDR 3000 per kg. The increase was obtained assuming the price before being saved IDR 22,250 per kg, and the sale price after saving is IDR 35,000 per kg. Value chain analysis shows that three stakeholders can use cold storage technology, namely farmers, collectors, and retailers in several people's markets in Kupang City. With the lowest profit and RC value in farmers, cold storage technology is more suitable for farmers compared to other actors. With cold storage technology, the chances of Soe's tangerine offering will remain under control.